Dexmedetomidine pretreatment alleviates propofol injection pain - He, Liang (Ups J Med Sci, 2014)
OBJECTIVE: The incidence of propofol injection pain during induction of general anesthesia varies from 28% to 90%. This prospective, randomized, double-blind, placebo-controlled study evaluated the effect of dexmedetomidine (DEX) for reducing the incidence and severity of propofol injection pain. METHODS: Patients undergoing elective surgical procedures were randomly allocated into seven groups of 30 patients each. Experimental treatments were intravenously administered over 10 min (total volume 10 mL) prior to intravenous propofol injection, as follows: group I, the control group, was given isotonic saline. Patients in groups II, III, and IV received DEX 0.25 µg/kg, 0.5 µg/kg, or 1.0 µg/kg, respectively, mixed with isotonic saline immediately before propofol injection. Patients in groups V, VI, and VII received DEX as above, but 5 minutes before propofol injection. Propofol consisted of 1% long-chain triglyceride propofol (2.5 mg/kg) injected at 1 mL/s. RESULTS: Median propofol injection pain score was 0.00 (IQR 0.00–3.00) in patients who received 1.0 µg/kg DEX 5 min before the propofol injection (group VII), and only 1 patient (of 30) in this group received a pain score >2. The median pain score and number of patients with pain scores >2 in group VII were both significantly less than in the control (group I; p = 0.000, both). There were no differences in either mean arterial pressure or heart rate at any time point after DEX injection among the groups. CONCLUSIONS: Pretreatment with intravenous DEX 1 µg/kg 5 min prior to injection of long-chain triglyceride propofol is effective and safe in reducing the incidence and severity of pain due to propofol injection.